Pembentukan Konsep Diri Mahasiswa Luar Jawa (Studi Deskriptif Kualitatif tentang Pembentukan Konsep Diri Mahasiswa Angkatan 2014 yang Berasal Dari Luar Jawa di Universitas Muhammadiyah Surakarta - Tyas, Aprilita Sekar Ayuning; , Palupi, MA; , Nur Latifah Umi Satiti, MA (2016)
The self concept is an important aspect in man as portraying themselves physically, psychologically and mentally. The self concept as a reference individuals to interact each other and adapt to their environment. With the new environment, such as students who come from outside Java in Surakarta Muhammadiyah University, made a new self-concept changes in her to adjust to the environment. In the new environment, there was the formation of self-concept in students. This research is a descriptive qualitative data collection using the technique of in-depth interviews. Informants were selected based on purposive sampling. Analysis of the data obtained using the model of Miles and Huberman and validity of the data itself is tested using triangulation. The results indicate that the formation of self-concept in students beyond Java influenced by interactions with an individual. Individuals who have a close attachment (significant other) as well as individuals - individuals who are formed into groups (generalized other) environment.